Penerapan Model Pembelajaran Explicit Instruction untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD GMIM II Taratara Kota Tomohon - Romi Junior Mongdong (Peneliti.net, 2021)
This study aims to describe the application of the Explicit Instruction learning model to improve social studies learning outcomes for fifth grade students of SD GMIM II Taratara. The research method uses Classroom Action Research (CAR) which consists of two cycles. This classroom action research was carried out in class V SD II Taratara with a total of 22 students consisting of 12 girls and 10 boys. The implementation of class action is carried out in two cycles. Based on the analysis of the data obtained by comparing each cycle, the data obtained in the first cycle there were several students whose scores were not satisfactory, this was influenced by the teaching model that had not been implemented properly. In this second cycle, the researcher gave more explanations with learning media that supported in the form of examples of pictures and provided feedback to students who always played so that the learning process was more active and the atmosphere in the classroom came alive and students were happy and had high curiosity during the process. learn how to teach. In the second cycle, student learning outcomes increased to (90%). Based on the discussion of the results of research conducted in class V SD GMIM Il Taratara, it can be concluded that applying the Explicit Instruction learning model in social studies learning can improve student learning outcomes at SD GMIM Il Taratara. The quality of student learning understanding is increasing. This is indicated by the results in each cycle. the first cycle reached 67% and got an increase in student learning outcomes in the second cycle reached 90%.